2015
DOI: 10.14527/kuey.2015.005
|View full text |Cite
|
Sign up to set email alerts
|

Dağıtılmış Liderliğin Okullardaki Görünümü: Bir Yapısal Eşitlik Modelleme Çalışması

Abstract: Bu çalışmanın temel amacı, liselerde görev yapan öğretmenlerin örgütsel güven, dağıtılmış liderlik, örgütsel destek algıları ve görev yaptıkları okulların okul başarısı arasındaki yapısal ilişkileri açıklayan teorik modeli test etmektir. Araştırma dört temel değişken arasında bir neden-sonuç ilişkisi bulunduğu düşüncesinden hareketle ilişkisel bir desende tasarlanmıştır. Araştırma örneklemi, tabakalı örnekleme yöntemiyle seçilen, Eskişehir büyükşehir sınırları içerisinde bulunan kamuya ait 22 farklı lisede gör… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
3
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
3
3
0
6
Order By: Relevance
“…Similar findings that directly or indirectly support this finding are also reported in the literature (Adıgüzelli, 2016;Beycioglu et al, 2012;Smylie et al, 2008;Yılmaz and Turan, 2015). This finding means that as school trust in administrator increases, distributed leadership behaviours also increase.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 87%
See 3 more Smart Citations
“…Similar findings that directly or indirectly support this finding are also reported in the literature (Adıgüzelli, 2016;Beycioglu et al, 2012;Smylie et al, 2008;Yılmaz and Turan, 2015). This finding means that as school trust in administrator increases, distributed leadership behaviours also increase.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 87%
“…In other words, trust felt towards administrators and distributed leadership in which contribution to school leadership is adopted would positively influence the school academic optimism. This finding of the study shows similarities with those reported in Yılmaz and Turan (2015) that reveal the predictive power of trust felt at school and distributed leadership practices over organisational support. Since distributed leadership emphasises aspects such as democratic participation, interaction, shared responsibility and improvement towards enhancing the quality of education at school, it is clear that they can be achieved with trust in administrator.…”
Section: Discussion Conclusion and Suggestionssupporting
confidence: 85%
See 2 more Smart Citations
“…Öte yandan, bazı araştırmacılar paylaşılan liderliği sadece yetki devri olarak değil aynı zamanda bireylerin liderlik kapasitesi geliştirebileceği ve gerektiğinde liderliği üstlenebileceği bir ortamın yaratılması olarak ele almıştır (Harris, 2008;Leithwood vd., 2009;MacBeath vd., 2004;Mayrowetz, 2008;Spillane ve Camburn, 2006). Bu ve başka çalışmalarda "paylaşılan liderlik" (Aslan ve Ağıroğlu-Bakır, 2015;Beycioğlu, 2010;Özer ve Beycioğlu, 2013;Uslu ve Beycioğlu, 2013) olarak ele alınmasına karşın, bu kavram belki de birebir çevirisinin de etkisiyle Türkiye'deki bazı çalışmalarda "dağıtılmış liderlik" (Oğuz, 2010;Yılmaz ve Turan, 2015) veya "dağıtımcı liderlik" (Baloğlu, 2011(Baloğlu, , 2012Baloğlu ve Karadağ, 2011;Özdemir, 2012) olarak da karşımıza çıkmaktadır. Ancak, Gronn'un da (2000) vurguladığı üzere bu kavram birilerini etkilemeden veya liderliğin diğerlerine dağıtılmasından ziyade grup dinamikleri içerisinde öğelerin etkileşiminden doğan bir olgu olarak değerlendirilmektedir.…”
Section: Introductionunclassified